Hubungan Model Project Based Learning dengan Kreativitas Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 1 Purba - Hier Inthersan Manullang; Risden Anakampun; Sandy Ariawan; Oloria Malau; Tiur Imeldawati (Jurnal Magistra, 2024)
The purpose of this research is to determine the relationship between the Project Based Learning learning model in increasing the learning creativity of Christian Religious Education for class VIII students at SMP Negeri 1 Purba. The method used in this research is an inferential descriptive quantitative method. The population was all class VIII students from class VIII-1 to VIII-6 who were Protestant Christians, totaling 155 people and a sample of 39 people was determined using purposive sampling technique. Data was collected using a positive closed questionnaire with 34 items, namely 16 items for variable proven by data analysis as follows: 1) positive relationship test obtained value rxy = 0.488 > r table(a=0.05,n=39) = 0.316 thus it is known that there is a positive relationship between variable X and variable Y, and the value rxy 0.488 if classified into the correlation coefficient is in the medium category. 2) Testing a significant relationship obtained a value of tcount= 3.397 > t table(a=0.05,dk=n-2=37)=2.021, thus there is a significant relationship between variable X and variable Y. So Ha says there is a positive relationship and the significance of the Project Based Learning model in increasing the Learning Creativity of Christian Religious Education for Class VIII Students of SMP Negeri 1 Purba was accepted and H0 which said there was no relationship was rejected.